Fungsi Sosialisasi Pendidik dalam Mencegah Perilaku Menyimpang Anak Asuh di Panti Desa SOS Meulaboh Aceh Barat - Rahfa Azzahra; Humaira Humaira; Musthakimah Musthakimah; Hertina Firza; Juliana Juliana; Sopar Sinambela (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the socialization function of educators and the efforts undertaken to prevent deviant behavior among foster children at SOS Children's Village Meulaboh, West Aceh. The study is based on the importance of educators' roles as agents of socialization in shaping the character, morals, and social behavior of foster children who come from diverse life backgrounds. This research employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving the head of the institution, educators/caregivers, and foster children at SOS Children's Village Meulaboh. The findings indicate that the socialization function of educators is carried out through role modeling, discipline development, the inculcation of moral and religious values, intensive communication, and behavioral supervision. Efforts to prevent deviant behavior are implemented through persuasive and educational approaches, religious activities, the cultivation of disciplined habits, and the involvement of children in various social activities. The continuous socialization process has proven effective in fostering positive behavior, increasing responsibility, discipline, and social interaction skills among foster children. Although challenges arise from differences in family backgrounds and psychological conditions, educators address these issues through individualized approaches and collaboration with relevant stakeholders. Therefore, the socialization function of educators plays a crucial role in preventing deviant behavior and in developing foster children into disciplined, morally responsible individuals who can adapt well to their social environment.